Notes on Indian Grasses-I. Distribution of Two less Known Species of Cynodon Rich - Jain, S. K. (Indian Forester, 1966)
The distribution of two less known species of Cynodon Rich. (Gramineae), viz., C. barberi Rang and Tad. And C. arcuatus J. S. Prest ex C. B. Presl is discussed. A key is provided for distinguishing these two species from C. dactylon (L.) Pers., 'Doob'.